Effect of Carbonization Temperature on Physical Properties and Specific Capacitance of Activated Carbon Derived from Banana Stem and Its Application as Supercapacitor Electrodes - Paweena Dulyaseree*; Hasanee Sama; Suraida Sada; Pundita Ukkakimapan; Visittapong Yordsri; Vichuda Sattayarut; Winadda Wongwiriyapan (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2022)
In this work, activated carbons (ACs) for electrodes supercapacitor applications were successfully synthesized from banana stem. Banana is one of the popular fruits that is easy to grow and most parts of the plant can be used. However, banana cultivation generates a lot of wastes, especially from the stem. Thus, using banana stem as raw material for ACs was investigated. The synthesis of AC consisted of 2 processes; carbonization and activation. The advantage of a two-step synthesis was the low weight loss of charcoal. Firstly, the carbonization process was conducted by varying the temperature between 300-600°C, and then inorganic elements were removed by treatment with 1 M sulfuric acid. After that, activation was conducted at 720°C under an argon atmosphere. The electrochemical properties of banana stem-derived ACs (BCH-ACs) were studied using sodium sulfate as an electrolyte. The BCH-ACs carbonized at 400°C showed the highest performance with a specific capacitance of 55.45 Fg-1, an energy density of 7.70 Whkg-1 and a power density of 133.94 Wkg-1. The highest specific capacitance of the BCH400-AC was likely due to the increase in the amount of oxygenated functional group, which facilitated the access of electrolyte ions into the electrode. These results suggest that banana stem can be used to synthesize ACs via carbonization at 400°C, and the ACs generated can be applied as electrode in supercapacitors. Keywords: banana stem; activated carbon; supercapacitor *Corresponding author: E-mail: paweena.d@yru.ac.th